KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI PENGARUH DIVERSIFIKASI OPERASIONAL PADA STRUKTUR MODAL - Wiryani, Dewa Ayu Sri Swasti Putri; Mertha, I Made (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The purpose of this study is to determine the effect of operational diversification within the capital structure and to determine whether the moderating influence of managerial ownership on operational diversified capital structure. This research was conducted at the Indonesian Stock Exchange, particularly in the property and real estate companies. The sampling method used nonprobability sampling method, using purposive sampling technique. The number of companies acquired are 10 companies. Total samples taken during the four years is as much as 40 observations. Data collection methods of data used is the method of documentation and literature study. The analysis technique used is a simple linear regression analysis and moderated regression analysis. The results of the analysis of operational research found that diversification does not affect the company's capital structure, and managerial ownership is not able to moderate the influence of operational diversification on capital structure.
Keywords: Diversified Operations, Capital Structure, Managerial Ownership